Nanostructured Zirconium‐Oxide Bioceramic Coatings Derived from the Anodized Al/Zr Metal Layers. Issue 14 (25th June 2021) - Fohlerova, Zdenka; Kamnev, Kirill; Sepúlveda, Marcela; Pytlicek, Zdenek; Prasek, Jan; Mozalev, Alexander
Abstract: Here, zirconium‐oxide ceramic coatings comprising arrays of 3D nanostructures are electrochemically synthesized, ranging in shape, size, spacing, and population density, termed as the nanomounds (ø≈65 nm), nanopillars (ø≈130 nm), and nanostumps (ø≈220 nm). The nanostructured coatings, alongside a flat ZrO2 anodic film, are explored as a potential biomaterial in experiments with Saos‐2 cells. All coatings reveal no cytotoxicity to living cells. The population density and spreading area of the cells, being the largest on the flat film, slightly decrease with increasing nanostructure dimensions. The cells progressively proliferate on all the surfaces, the nanomounds and, especially, nanopillars promoting the best viabilities and proliferation rates. The flat, nanomound, and nanopillar coatings promote the well‐defined organizations of actin filaments across the entire cell bodies with no disruption in the cytoskeletal network and the mature large dash‐shaped focal adhesions. The highest activity of alkaline phosphatase and the biggest deposition of a mineralization‐competent extracellular matrix occur on the nanopillar array, the other nanostructures showing a better result than the flat coating, though. The differences, paradoxes, and regularities in the cell responses are explained through the detailed consideration of the coating morphologies, surface chemistries, and processes at the cell/surface interfaces. Abstract : Several distinctive types of nanostructured zirconium‐oxide coatings with unique surface chemistries and morphologies are synthesized via the self‐organized anodizing of sputter‐deposited aluminum‐on‐zirconium layers and tested as a novel bioceramic material in experiments with Saos‐2 cells disclosing diverse effects of the nanoscale cell‐oxide interactions.